Peningkatan Literasi Digital Guru melalui Pemanfaatan Teknologi Edukasi - Gusty, Sri; Syafar, A.Muhammad; Londongsalu, Jefryanto; Batara, Chris; Waris, Milawaty; Asmeati, Asmeati (Penerbit Widina, Widina Media Utama, 2025)
This activity aimed to enhance the digital literacy of junior high school teachers by introducing practical skills in educational technology and the use of artificial intelligence (AI)-based tools in the classroom. The community service program was conducted face-to-face in the form of a hands-on workshop using the lesson study approach (Plan-Do-See). The partners in this activity were the Tamalate Sub-district Government and several junior high schools in Makassar. It was held on July 16, 2025, at the Tamalate Sub-district Office Hall and attended by approximately 25 teachers representing various schools. Participants used their own devices for direct practice. Evaluation results indicated an improvement in teachers’ abilities after the training. Before the program, only 28% of participants were able to create Google Forms, which increased to 76% after the training. Skills in managing Google Classroom rose from 16% to 72%, using Google Sheets from 12% to 68%, and collaborating via Google Docs from 20% to 70%. The training outcomes reflected high enthusiasm, with participants demonstrating competence in operating Google Forms, Google Classroom, and Google Spreadsheets effectively. Many expressed strong interest in applying AI tools for content development and enhancing classroom interaction. Overall feedback was positive, although some challenges were noted, including limited time to explore AI in depth, internet access issues, and varying levels of digital proficiency among participants. The program successfully achieved its objective of improving teachers’ digital literacy, as evidenced by the increased skills in Google Forms, Classroom, Sheets, and Docs. Moreover, participants showed strong enthusiasm in utilizing AI to support teaching, making the program effective in equipping teachers with practical competencies while fostering readiness to face the challenges of 21st-century education.ABSTRAKKegiatan ini bertujuan untuk meningkatkan literasi digital guru SMP dengan memperkenalkan keterampilan praktis dalam teknologi pendidikan dan penggunaan alat berbasis kecerdasan buatan (AI) di kelas. Kegiatan pengabdian kepada masyarakat ini dilaksanakan secara tatap muka (luring) dalam bentuk workshop berbasis praktik langsung dengan pendekatan lesson study (Plan-Do-See). Mitra kegiatan adalah Pemerintah Kecamatan Tamalate dan beberapa sekolah menengah pertama di Kota Makassar pada tanggal 16 Juli 2025 di aula kantor Kecamatan Tamalate, Makassar, yang diikuti oleh sekitar 25 guru perwakilan sekolah. Para peserta menggunakan perangkat pribadi untuk praktik langsung. Hasil evaluasi menunjukkan adanya peningkatan kemampuan guru setelah pelatihan. Sebelum kegiatan, hanya 28% peserta mampu membuat Google Form, meningkat menjadi 76% setelah pelatihan. Kemampuan mengelola Google Classroom naik dari 16% menjadi 72%, penggunaan Google Sheets dari 12% menjadi 68%, serta kolaborasi melalui Google Docs dari 20% menjadi 70%. Hasil pelatihan menunjukkan antusiasme tinggi, dengan kemampuan peserta dalam mengoperasikan Google Forms, Google Classroom, dan Google Spreadsheet secara efektif. Banyak peserta menyatakan minat besar untuk menerapkan alat AI dalam pembuatan konten dan peningkatan interaksi pembelajaran. Umpan balik umumnya positif, meskipun terdapat kendala seperti keterbatasan waktu dalam mengeksplorasi AI secara mendalam, permasalahan akses internet, serta perbedaan tingkat kemampuan digital peserta. Pelatihan ini berhasil meningkatkan literasi digital guru sesuai tujuan kegiatan, ditunjukkan oleh peningkatan keterampilan pada Google Forms, Classroom, Sheets, dan Docs. Peserta juga antusias memanfaatkan AI untuk mendukung pembelajaran, sehingga program ini efektif membekali guru dengan kemampuan praktis sekaligus menumbuhkan kesiapan menghadapi tantangan pendidikan abad ke-21.